EMOTIONAL LEXICONS IN FOOD AND DRINK ADVERTISEMENTS (Journal of Foreign Language Studies, 2024)
The effectiveness of advertisement content is one of the most significant factors affecting consumers’ affective and behavioral intentions. Consumption emotions which consumers experience before, during and after using a product partly derive from their exposure to the advertisement. Various consumption emotions for different food products and experiences have been explored and validated. However, there has been little research that scrutinizes emotional lexicons in advertisements and how these lexicons affect consumer behaviors. This empirical research adopted content and thematic analysis to explore the emotional lexicons used in food and beverage advertisements. The study examined advertisers’ perspectives of emotional lexicon and the degree of influence on consumers’ perceptions and behaviors. The findings showed that three themes of the emotional words and expressions were used in food and beverage advertisements: sensory, affective, and behavioral evocative. This study made theoretical contributions to the knowledge of consumption emotion and provided valuable insights into the method and process of creating emotional lexicon. It also proposed a working list of emotional lexicons helpful for food and beverage advertising
Keywords: emotion; lexicon; advertising; sensory; behavioral triggering